Endogenous Mechanisms of Craniomaxillofacial Repair: Toward Novel Regenerative Therapies - desJardins-Park, Heather E.; Mascharak, Shamik; Longaker, Michael T.; Wan, Derrick C. (Frontiers in Oral Health, 2021)
In the fields of oral and craniomaxillofacial surgery, regeneration of multiple tissue types—including bone, skin, teeth, and mucosal soft tissue—is often a desired outcome. However, limited endogenous capacity for regeneration, as well as predisposition of many tissues to fibrotic healing, may prevent recovery of normal form and function for patients. Recent basic science research has advanced our understanding of molecular and cellular pathways of repair in the oral/craniofacial region and how these are influenced by local microenvironment and embryonic origin. Here, we review the current state of knowledge in oral and craniomaxillofacial tissue repair/regeneration in four key areas: bone (in the context of calvarial defects and mandibular regeneration during distraction osteogenesis); skin (in the context of cleft lip/palate surgery); oral mucosa (in the context of minimally scarring repair of mucosal injuries); and teeth (in the context of dental disease/decay). These represent four distinct healing processes and outcomes. We will discuss both divergent and conserved pathways of repair in these contexts, with an eye toward fundamental mechanisms of regeneration vs. fibrosis as well as translational research directions. Ultimately, this knowledge can be leveraged to develop new cell-based and molecular treatment strategies to encourage bone and soft tissue regeneration in oral and craniomaxillofacial surgery.